2020
DOI: 10.1002/smtd.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Alluaudite Battery Cathodes

Abstract: Rechargeable batteries have emerged as ubiquitous and indispensable technologies of the 21st century, propelling myriads of consumer electronics and ushering a new era of electric vehicles and stationary grid storage. Since the commercialization of Li‐ion batteries by SONY (approximately in the year 1991), the secondary battery sector has seen unprecedented growth with diverse applications touching global populations across socioeconomic strata. There is a steady quest to develop a wide range of batteries to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 110 publications
1
11
0
2
Order By: Relevance
“…Alluaudites, named after its discoverer Franҫois Alluaud II, are a group of alkali metal phosphate-based naturally occurring minerals having open frameworks as well as broad tunnels for easy alkali ion passage [7]. The general formula of alluaudite-based materials can be written as A (1)A( 2)M(1)M(2) 2 (XO 4 ) 3 , where A denotes the alkali ions, M denotes the transition metal ions, and X could be S, P, As, V, Mo, or W [8]. A and M (1) sites are occupied by monovalent (Na + , Li + ) or divalent cations (Ca 2+ , Mg 2+ ) while the M(2) site can be filled with divalent (Mn 2+ , Fe 2+ ) or trivalent cations (Mn 3+ , Fe 3+ , In 3+ ).…”
Section: Introductionmentioning
confidence: 99%
“…Alluaudites, named after its discoverer Franҫois Alluaud II, are a group of alkali metal phosphate-based naturally occurring minerals having open frameworks as well as broad tunnels for easy alkali ion passage [7]. The general formula of alluaudite-based materials can be written as A (1)A( 2)M(1)M(2) 2 (XO 4 ) 3 , where A denotes the alkali ions, M denotes the transition metal ions, and X could be S, P, As, V, Mo, or W [8]. A and M (1) sites are occupied by monovalent (Na + , Li + ) or divalent cations (Ca 2+ , Mg 2+ ) while the M(2) site can be filled with divalent (Mn 2+ , Fe 2+ ) or trivalent cations (Mn 3+ , Fe 3+ , In 3+ ).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] Their general formula is A2M(1)2M(2)(XO4)3 for X = P, V, and A2M(1)M(2)(XO4)3 for X = S, with A = Li, Na. The A2M(1)2M(2)(XO4)3 structure (monoclinic C2/c space group 40 ) is shown in Figure 1a. Alluaudites exhibit edgesharing MO6 octahedra that form kinked one-dimensional (1D) chains of M(2) octahedral pairs alternating with an M(1) octahedron (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The values varied from 50 to 140 mAh/g, while most of the papers reported values about 100 mAh/g. A review of such parameters can be found, e.g., in [ 7 ]. Among the compositions containing iron, vanadium, and manganese, e.g., Na Fe V(PO ) [ 8 ] and Na Mn V(PO ) [ 9 ] have been synthesized and studied.…”
Section: Introductionmentioning
confidence: 99%